ESG Rating and Firm Value in Emerging Market: Investigating the Mediating Role of Financial Performance - Wahyono, Wahyono; Laga, Anastasya; Kurniawati, Rizki; Sari, Dwi Rahmita; Mukhzarudfa, Mukhzarudfa; Kusumastuti, Ratih; Putra, Wirmie Eka (Asian Journal of Applied Business and Management, 2024)
This study examines the impact of ESG Rating on Firm Value, with Financial Performance as a mediating variable, using a sample of companies included in the IDX ESG Leaders index for the years 2021–2023. The analysis was conducted using PROCESS Macro and bootstrapping methods to identify the direct and indirect effects of ESG practices on Firm Value. The findings reveal that ESG Rating does not have a direct effect on Firm Value, nor does Financial Performance mediate this relationship. These results suggest that in emerging markets like Indonesia, the direct financial benefits of ESG practices are not fully recognized by investors, possibly due to a lower level of awareness and appreciation of sustainability. This study offers insights into the challenges and opportunities for ESG implementation among companies in emerging markets to enhance long-term firm value.